Age identity, social influence and socialization through physical activity in elderly people living in a nursing home - Prevc, Petra (Array, 2009)
Abstract: Elderly people perceive their own ageing in very different ways and the aim of the present study was to explore age identity, the perception of »old age«, the role of physical activity in the socialization of elderly people and social influences on physical activity in elderly people living in a nursing home. Questionnaires were answered by 75 nursing home residents (79±8 years old; 19 males, 56 females), coming from two different Slovenian regions. Subjective age (»felt age«) was on average 5.5 years less than chronological age. Neither increasing chronological age nor subjective age was significantly correlated with a negative perception of health. Subjective age was neither correlated with any of the statements related to well-being and satisfaction with life. The importance of health in old age was confirmed by significant correlation of health status with perception of one’s well-being and satisfaction with life. Interestingly, the age at which one perceives a person as having become old was not significantly related to one’s own age. Nursing home residents in general associate old age with physical impairment and poor health. Slight differences between genders were noted; men grade retirement and communication difficulties with younger people as more prominent in old age. Interaction with other residents seems to be an important component of physical activity, as participants grade the importance of socializing during exercise quite highly; no significant differences between regions nor between men and women were noted. The social influence on physical activity did not differ significantly between genders and observed regions; the presence of negative social influence was relatively low. Furthermore, in the third period of life, physical activity plays an important socialization role and is, at the same time, influenced by the beliefs and ideas of the environment